How Can the Least Developed Member Countries of ASEAN Benefit from the 4th Industrial Revolution? - SMITH , Robert Brian (Walailak Journal of Science and Technology (WJST), 2021)
The ASEAN members Cambodia, Lao DPR, and Myanmar have been classified by the United Nations as least developed countries, with many of their citizens living below the poverty line, and its workers predominantly rural. This paper seeks to ascertain how these 3 countries can benefit from the 4th Industrial Revolution (4IR) and the changes required so that their citizens can benefit from increasing economic prosperity, improved social well-being, rising human values, and environmental protection. In this context, the 4IR can be defined as the revolutionary change when information technology proliferates in all industries and is the connection between technology and the market. An analysis of the contemporary data and reports, mainly from the Asian Development Bank and the World Bank, has identified niches which each of the economies can develop on the path to the 4IR. The analysis has also identified a common impediment to progress: namely, the current state of development of the educational system, with curricula which are often not relevant to the needs of the current and future market, and the methods of their delivery in both formal education and industrial training. The changes must ensure that recipients are encouraged to develop skills in critical thinking and communication, including the ability to ask questions. Finally, the paper suggests an appropriate model for the 4IR and the development stages for these economies as they move along the path to reach this goal.